The Exclusive Economic Zone: The Geopolitical Role of the International Court of Justice in the Peru-Chile and Nicaragua-Colombia Cases (2001-2014) - Garrido-Quiroz, A (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2022)
The Exclusive Economic Zone (EEZ) is one of the few legal and geopolitical concepts built from the political south in international relations. In Latin America, understanding the role of the International Court of Justice (ICJ) as an agent that reinterprets the legal-geopolitical discourse of the litigating States, in order to later redistribute power, is essential to understand the dynamics of the maritime limits of the region. Our point is that the United Nations Convention on the Law of the Sea (UNCLOS) does not improve the security of maritime borders before the ICJ considering the close connection between international custom and the content of the treaty. Thus this research is developed from a comparative geopolitical analysis for the 1939-2014 period, and is built on the basis of a non-experimental qualitative methodology focused on the geopolitical analysis of discourse.